A EFEKTIVITAS PIJAT LAKTASI TERHADAP VOLUME ASI PADA IBU POSTPARTUM DI BPM LEDI ELIANI DESA TANDUN: Efektifitas Pijat Laktasi, BPM Ledi Eliani - Andria, Andria; Karmila; Julita; Putri, Yuriska; Nurmawilis, Nova; Fifti, Dinda Aura (AHM Center, 2025)
Breast milk is the best food for babies, in breast milk there are multiple benefits, namely: nutritional, physiological and psychological benefits for babies. Preparing for breastfeeding earlier is better and ready to breastfeed. It is recommended that breastfeeding be prepared from the antenatal period. Successful breastfeeding is supported by physical, psychological preparation and lactation management. Based on the results of data at BPM Ledi Eliani, Tandun village, Tandun District, Rokan Hulu Regency, there were 10 mothers who gave birth at BPM Ledi Eliani for the last 3 months. The purpose of the study was to determine the effectiveness of lactation massage. This study uses a pre-experiment method with a research design of one group pre test and post test, using a checklist sheet and a brest pump. The population of this study was all mothers who parted at BPM Ledi Eliani and had difficulty leaving breast milk totaling 10 people The sampling technique in this study uses a non-probability sampling technique, namely using saturated samples, namely all population numbers are used as a sample of 10 people. The results of the study from data analysis were the average volume of breast milk of postpartum mothers before lactation massage was (19.50) while the average volume of breast milk of postpartum mothers after lactation massage was (43.00). Based on the results of the T-Dependent statistical test data, a P-value of 0.000 < 0.05 was obtained, which means that there is an effect of lactation massage on increasing breast milk volume in post-patrum mothers at BPM Ledi Eliani, Tandun Village, Tandun District, Rokan Hulu Regency. It is hoped that the results of this study can be a source of information and a basis for knowledge that there is a link between the effect of lactation massage on increasing breast milk volume.